THE EVALUATION OF OUTSOURCING USE ON UKRAINIAN RAILWAY TRANSPORT - Stasiuk, O. M. (Science and Transport Progress, 2009)
The estimate of outsourcing possibilities on the railway transport of Ukraine is realized. The kinds of activities, which are promising for transfer through outsourcing to small enterprises, are proposed.